AKULTURASI NILAI HUKUM ISLAM DALAM TRADISI MAPPACCI PADA MASYARAKAT DESA LIMAPOCCOE KABUPATEN MAROS - Asma, Fauziah; Alwi, Zulfahmi; Ibnu Izzah (Universitas Islam Negeri Alauddin Makassar, 2023)
Abstract The main problem in this study is the acculturation of Islamic legal values ​​in the mappacci tradition in the community in Limapoccoe Village, Maros Regency. This study aims to explain the procession of the Mappacci tradition in the Limapoccoe Village community, Maros Regency and the Islamic Legal Values ​​acculturated in the Mappacci tradition in the Limapoccoe Village community. The type of research used is qualitative research, namely field research using a cultural approach, a syar'i approach, and a sociological approach, then the data collection methods used are interviews, observation and documentation. The results of this study indicate that the mappacci procession does not violate the provisions of Islamic teachings and is a symbol of self-purification and cleansing of the soul of the prospective bride and groom before undergoing domestic life and obtaining blessings from relatives and can be blessed by Allah SWT. The implication of this research is that the procession in the Mappacci tradition should be carried out because it has become a hereditary habit from the past and there are several Islamic legal values ​​that have been acculturated into the Mappacci tradition including: the value of divinity, the value of ta'awun, the value of tolerance, the value of freedom and the value of patience or istiqamah. Suggestions from the author so that this mappacci tradition can be preserved and maintained in order to avoid things that violate the provisions of Islam. Keywords: Acculturation, Islamic Law, Mapppacci Procession